Exploring cyber security behavioral practices among secondary school students following the MyDigital Maker Champion program in Putrajaya, Malaysia - Intan Diana; Ismail, Ismi Arif; Mohd Zairul (Human Resource Management Academic Research Society, 2024)
The practice of cyber security behaviour is the act of protecting digital devices and oneself from cyber threats. Cases of cyber threats increasing year by year have negatively affected the victims, such as loss of money, properties and emotional disturbance. Furthermore, teenagers are the most internet users at risk of being exposed to cyber threats. By using the Technology Threat Avoidance Theory, the Knowledge, Attitude, and Practice Model, and the Theory of Planned Behaviour, this study explores the problem of cyber threats that occurs to high school students who follow the MyDigital Maker Champion program in Putrajaya, Malaysia, understanding the students' cybersecurity behaviour practices as well as exploring methods of overcoming the problem of cyber threats among students. Next, this study proposes a cybersecurity behavioural framework with components to solve cyber threats among the students. This study uses an interpretive paradigm with a case study design. Qualitative data was obtained through interviews, focus groups, and archival document analysis of cyber security experts, teachers, school counsellors, and high school students who followed the MyDigital Maker Champion program. Data were analysed by conducting a thematic analysis. The study's findings show that there are four types of cyber threats, from the point of view of 1) the Information Technology Policy Act, 2) media content, 3) writing, and 4) psychology. In addition, there are two forms of cyber security behaviour practices, which are 1) strict cyber security practices and 2) being ethical in surfing cyberspace. This study also found three methods to overcome the problem of cyber threats, namely 1) awareness campaigns, 2) receiving support from subjective norms, and 3) implementing cyber security laws specifically for the teenagers. The findings of this study also form a framework of cyber security behaviour that help to overcome the problem of cyber threats that occursamong high school students. In conclusion, the findings of this study can guide students, teachers, and the Malaysian Ministry of Education to improve the solution method in facing cyber threats among high school students through education and produce a future learning system that is more advanced, quality and guaranteed security from any form of cyber-attack.